Control of an Autonomous Hybrid Microgrid as Energy Source for a Small Rural Village - Americo Joaquim Lampiao; Tomonobu Senjyu; Atsushi Yona (International Journal of Electrical and Computer Engineering (IJECE), 2017)
Nowadays, the exhaustion of electricity power in rural areas is becoming an important issue for many African Nations. Moreover, challenges include the high cost of extending the power grid to these locations, the economic health of the utilities and lack of revenue in impoverished villages. Numerous new initiatives are being implemented in the countries some of them co-financed by international organizations. In this paper, the hybrid microgrid is carried out as a feasible solution for a small rural village. A model of hybrid microgrid consisting of combination of photovoltaic (PV) panels and battery energy storage (BES) and a control system for managing the components of entire system to feed the village as local load is proposed. The control system must avoid the interruptions of power delivered to the consumers (village) and, therefore, good quality and reliability of system is required. The PI controllers are used to regulate the voltage and current using three-phase dq transformation, while the parameters are determined using Ziegler-Nichols tuning method. The effectiveness of the proposed method is verified by simulation results given by the Matlab/SimPowerSystems environment.